(untitled) (Indonesian Sports Justice Review, 2024)
Major sporting events in Indonesia, such as the Southeast Asian Games or the Indonesian Open, often serve as powerful symbols of national pride and unity. However, these events also reveal underlying social inequities that persist within the country. This paper examines how sports events reflect and sometimes exacerbate social justice issues, including ethnic inequality, regional disparities, and gender discrimination. It focuses on the ways in which the media, sponsorships, and state involvement in these events contribute to reinforcing or challenging social hierarchies. The study critically assesses how the representation of athletes from marginalized communities is often overshadowed by the media spotlight on elite performers from more privileged backgrounds. By exploring the intersection of sports, national identity, and social justice, the paper offers policy suggestions to ensure that national sporting events are used as platforms for promoting inclusivity and equity.